Kajian Sosiologi Dalam Naskah Drama Roh Karya Wisran Hadi Dan Relevansinya Dalam Materi Ajar Bahasa Indonesia Pada Jenjang Sekolah Menengah Atas - Ajeng Maryam; Anjani Lintang Pertiwi; Chica Chaswati; Moh. Hafidz Assidiq Syam; Nurohmah Nurohmah; Adita Widara Putra (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to examine in more depth how the drama script "Roh" by Wisran Hadi can be relevant to Indonesian language teaching material at the high school level, using sociological approach. The method used in this research is descriptive method. The data sources in this research are the text of the drama script "Roh" as well as secondary sources such as relevant articles, journals and books. Data collection techniques include literature study and content analysis. This research concludes that the literary sociology study of the drama script "Roh" by Wisran Hadi has great potential to enrich Indonesian language learning in schools. Through this approach, students not only learn about literature, but also about history, culture, and social issues that are relevant to their lives